An Exploratory Study on How Civil Servants Resolve the Paradoxes of the "Iron Cage" of Bureaucracy in a "VUCA" World - Vinh Giang, Hoang (Policy & Governance Review, 2025)
This study explores how Vietnamese civil servants address the complex paradoxes created by the "iron cage" of bureaucracy, particularly within the volatile, uncertain, complex, and ambiguous (VUCA) environment of modern public administration. Using in-depth qualitative interviews with 30 public officials from diverse regions and roles, this study uncovered a nuanced spectrum of adaptive strategies, including compliance, accommodation, collectivization, inertia, and distortion. By integrating classical and contemporary bureaucracy theories with real-world accounts, this study highlights how traditional hierarchical cultures and rigid procedures simultaneously support stability and impede effective adaptation. Comparative analysis of global and regional public sector reforms reveals both the unique and shared dilemmas faced by Vietnamese officials. The findings have significant implications for policy reforms, organizational change, and future research on state capacity, accountability, and innovation in developing countries. This paper argues that successful bureaucratic adaptation in a VUCA world requires balancing institutional orders with responsible discretion and fostering a culture of learning, resilience, and ethical public services.